Plant Growth Promoting Rhizobacteria Alleviate Aluminum Toxicity and Ginger Bacterial Wilt in Acidic Continuous Cropping Soil - Zhang, Shuting; Jiang, Qipeng; Liu, Xiaojiao; Liu, Liehua; Ding, Wei (Frontiers in Microbiology, 2020)
Long-term monoculture cropping is usually accompanied by soil acidification and microbial community shifts. Soil aluminum ions are dissolved under acidic condition (pH < 5.0) and the resulting aluminum bio-availability can cause toxic effects in plants. In this study, we investigated the bacterial community compositions and aluminum toxicity in fields monocultured with ginger for 35 years, 15 years and one year. Within these fields are ginger plants without and with ginger bacterial wilt disease. The results confirmed that the degree of aluminum toxicity in the diseased soil was more severe than that in the healthy soil. Continuous cropping can significantly increase the bacterial diversity and change the bacterial community composition of ginger rhizosphere soil. The relative abundance of plant growth promoting rhizobacteria (PGPRs) was increased in the soils used for the continuous cropping of ginger. Additionally, aluminum toxicity had a significant positive correlation with Bacillus, Pseudomonas, Arthrobacter and Serratia in healthy soils. Based on these results, aluminum stress may stimulate the increase of PGPRs (Bacillus, Pseudomonas, Arthrobacter and Serratia), thereby alleviating ginger aluminum toxicity and bacterial wilt in extremely acidic soil (pH < 4.5).